Circular RNA circNOL10 Inhibits Lung Cancer Development by Promoting SCLM1‐Mediated Transcriptional Regulation of the Humanin Polypeptide Family. Issue 2 (16th November 2018) - Nan, Aruo; Chen, Lijian; Zhang, Nan; Jia, Yangyang; Li, Xin; Zhou, Hanyu; Ling, Yihui; Wang, Zhishan; Yang, Chengfeng; Liu, Sijin; Jiang, Yiguo
Abstract: circNOL10 is a circular RNA expressed at low levels in lung cancer, though its functions in lung cancer remain unknown. Here, the function and molecular mechanism of circNOL10 in lung cancer development are investigated using in vitro and in vivo studies, and it is shown that circNOL10 significantly inhibits the development of lung cancer and that circNOL10 expression is co‐regulated by methylation of its parental gene Pre‐NOL10 and by splicing factor epithelial splicing regulatory protein 1 (ESRP1). circNOL10 promotes the expression of transcription factor sex comb on midleg‐like 1 (SCML1) by inhibiting transcription factor ubiquitination and thus also affects regulation of the humanin (HN) polypeptide family by SCML1. circNOL10 also affects mitochondrial function through regulating the humanin polypeptide family and affecting multiple signaling pathways, ultimately inhibiting cell proliferation and cell cycle progression, and promoting the apoptosis of lung cancer cells, thereby inhibiting lung cancer development. This study investigates the functions and molecular mechanisms of circNOL10 in the development of lung cancer and reveals its involvement in the transcriptional regulation of the HN polypeptide family by SCML1. The results also demonstrate the inhibitory effect of HN on lung cancer cells growth. These findings may identify novel targets for the molecular therapy of lung cancer. Abstract : This study provides new evidence for the molecular mechanism whereby circRNAs may affect transcriptional regulation in lung cancer cells, and also reveals that circNOL10 inhibits lung cancer development by promoting SCLM1‐mediated transcriptional regulation of the humanin (HN) polypeptide family. The results also demonstrate the inhibitory effect of HN on lung cancer growth.